Additionality revisited: guarding the integrity of market mechanisms under the Paris Agreement. (26th November 2019) - Michaelowa, Axel; Hermwille, Lukas; Obergassel, Wolfgang; Butzengeiger, Sonja
ABSTRACT: The Paris Agreement requires mitigation contributions from all Parties. Therefore, the determination of additionality of activities under the market mechanisms of its Article 6 will need to be revisited. This paper provides recommendations on how to operationalize additionality under Article 6. We first review generic definitions of additionality and current approaches for testing of additionality before discussing under which conditions additionality testing of specific activities or policies is still necessary under the new context of the Paris Agreement, that is, in order to prevent increases of global emissions. We argue that the possibility of 'hot air' generation under nationally-determined contributions (NDCs) requires an independent check of the NDC's ambition. If the NDC of the transferring country does contain 'hot air', or if the transferred emission reductions are not covered by the NDC, a dedicated additionality test should be required. While additionality tests of projects and programmes could continue to be done through investment analysis, for policy instruments new approaches are required. They should be differentiated according to type of policy instrument. For regulation, we suggest calculating the resulting pay-back period for technology users. If the regulation generates investments exceeding a payback period threshold, it could be deemed additional. Similarly, carbon pricing policies that generate a carbon price exceeding a threshold could qualify; for trading schemes an absence of over-allocation needs to be shown. The threshold should be differentiated according to country categories and rise over time. Key policy insights Without additionality testing, market mechanisms under the Paris Agreements might lead to an international diffusion of 'hot air'. To avoid this, an independent assessment of NDC ambition is in order. Otherwise, activities under the mechanisms need to undergo specific additionality tests. Additionality testing of projects and programmes should build on the experience developed under the Kyoto Protocol mechanisms. Bold approaches are needed for assessing additionality of policies. To avoid cumbersome assessment of all activities triggered by such policies, highly aggregated approaches are suggested, ranging from payback period thresholds for technologies mandated by regulation to minimum price levels triggered by carbon pricing policies. Over time, the stringency of threshold values should increase.